The values of character education in the pakeliran art “Lord Shiva Saves the Universe” - Komang Sekar Marhaeni; Ni Ketut Dewi Yulianti; I Ketut Garwa (Institut Seni Indonesia Denpasar, 2022)
The purpose of this paper is to analyze the values of character education in the traditional art of “Lord Shiva Saves the Universe” and the moral messages contained in it, which are beneficial not only for humanists and artists, but also for activists in the field of character education. The method used is a qualitative by analyzing the performance of